Greater event rates in high-risk patients with a history of heart disease: from the Systolic Blood Pressure Intervention Trial (SPRINT). (14th October 2021) - Pareek, M; Byrne, C; Mikkelsen, A D; Dyrvig Kristensen, A M; Vaduganathan, M; Biering-Sorensen, T; Kragholm, K H; Mortensen, M B; Singh, A; Olsen, M H; Bhatt, D L
Abstract: Background: The Systolic Blood Pressure Intervention Trial (SPRINT) found that intensive versus standard blood pressure (BP) control reduced cardiovascular (CV) morbidity and mortality in patients at high CV risk. Effects were consistent among patients with and without prevalent CV disease. However, it is unknown whether the benefits and risks of intensive BP control are affected by the specific type of heart disease. Purpose: To assess the risks of incident CV events and safety events in patients with individual types of heart disease, and to assess if the presence of heart disease modified the effect of intensive versus standard BP control. Methods: SPRINT was a randomized, controlled trial comprising 9, 361 individuals ≥50 years of age at high CV risk, without diabetes, and with a systolic BP 130–180 mmHg. Participants were randomized to intensive or standard BP control. The primary efficacy endpoint was the composite of myocardial infarction, other acute coronary syndromes, stroke, heart failure, or death from CV causes. The primary safety endpoint was the composite of serious adverse events. We assessed event risk in patients with self-reported heart disease versus those without and further assessed the safety and efficacy of intensive BP control, including relevant interactions, in these individuals, using multivariable Cox proportional-hazards regression. Results: Of 9361 participants, 326 (3.5%) reported a history of congestive heart failure, 760 (8.1%) of myocardial infarction, 1206 (12.9%) of angina, and 1830 (19.6%) of atrial fibrillation, atrial flutter, or irregular heartbeat. The prevalence of these conditions did not significantly differ between patients randomized to intensive versus standard BP control (P>0.05 for all). At median 3.2 years (range 0–4.8 years), congestive heart failure (adjusted hazard ratio [aHR], 1.94, 95% confidence interval [CI], 1.45–2.61; P<0.001), myocardial infarction (aHR, 1.73, 95% CI, 1.33–2.25; P<0.001), angina (aHR, 1.41, 95% CI, 1.09–1.84; P=0.01), and atrial fibrillation, atrial flutter, or irregular heartbeat (aHR, 1.36, 95% CI, 1.12–1.64; P=0.002) were all independently associated with the primary endpoint (Figure). All conditions except prior myocardial infarction were also associated with composite serious adverse events (P=0.24 for myocardial infarction, P<0.05 for all others). A history of angina modified the efficacy of intensive versus standard BP control, i.e., patients without angina appeared to benefit from intensive BP control (aHR, 0.66, 95% CI, 0.54–0.80; P<0.001) while those with angina did not (aHR, 1.04, 95% CI, 0.76–1.44; P=0.80) (P=0.02 for interaction). No significant interactions were detected for the primary safety endpoint. Conclusions: In SPRINT, a history of any type of heart disease was associated with a greater risk for both efficacy and safety events. Patients with angina did not appear to derive benefit from intensive BP control. Funding Acknowledgement: Type of funding sources: None.